2015
DOI: 10.14419/ijbas.v4i3.4630
|View full text |Cite
|
Sign up to set email alerts
|

PCR for detection of virulence and antibiotic resistance genes of coagulase positive staphylococcus aureus from clinical mastitis in Egypt

Abstract: <p>Coagulase positive <em>Staphylococcus aureus</em> is the most frequently bacterial pathogen causing clinical mastitis in cattle. In this work 120 milk samples were collected from cattle suffering from clinical mastitis. The result revealed that S. aureus was 35 isolates (29.16%) and other staphylococci were 13 isolates (10.84%). The application of PCR was effectively in detection of Coa. SpA, mecA and blaZ genes of <em>S. aureus</em> by amplification at a single amplicon at 630… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous report supported the importance of nuc gene as gold standard for S. aureus identification (David et al, 2010). Regarding to the detection of mecA gene in most S. aureus isolates in our study which was demonstrated in clinical mastitis isolates by (Abdeen et al, 2015) who amplified mecA gene in all tested S. aureus isolates. While lower prevalence of mecA gene 16% was recorded in China (Qu et al, 2019).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous report supported the importance of nuc gene as gold standard for S. aureus identification (David et al, 2010). Regarding to the detection of mecA gene in most S. aureus isolates in our study which was demonstrated in clinical mastitis isolates by (Abdeen et al, 2015) who amplified mecA gene in all tested S. aureus isolates. While lower prevalence of mecA gene 16% was recorded in China (Qu et al, 2019).…”
Section: Discussionmentioning
confidence: 57%
“…Regarding to the identification of S. aureus isolates through biochemical tests, all the tested isolates were tested by coagulase, catalase and sugar fermentation tests. This was previously applied and described by (Abdeen et al, 2015;Elmaghraby et al, 2018) who tested all isolates of S. aureus by coagulase, catalase and fermentation activities.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular identification of the coa gene in S. aureus strains was performed through amplification of the coa gene at (600–1000) bp. The use of the coa gene to detect S. aureus strains from milk origin was previously reported in two studies [ 37 , 41 ] which amplified the coa gene from mastitic milk and dairy products at 630 and 750 bp. Moreover, Javid and colleagues [ 42 ] detected the coa gene at 514 bp, 595 bp, 757 bp, and 802 bp.…”
Section: Discussionmentioning
confidence: 99%